Design of a Web-Based Information System for Tracking Oil Palm Fruit Invoices - Indra; Syarif Subandi (oneamrd (One a Mllions Dreams Corporation), 2026)
Financial administration services—specifically regarding the processing of invoices for raw oil palm fresh fruit bunches (FFB) purchased from third parties—constitute a vital element of palm oil industry operations. At PT HPI-Agro, the process of tracking invoices from external suppliers (such as cooperatives, CVs, and limited liability companies) is currently performed manually using Microsoft Word, Microsoft Excel, and conventional bookkeeping, lacking an integrated monitoring system. This situation leads to inefficient inter-departmental coordination, resulting in payment delays of 10 to 14 working days. This study aims to design a web-based invoice tracking information system to accelerate administrative workflows and provide real-time updates on payment status. The system was designed using the Systems Development Life Cycle (SDLC) methodology, with analysis conducted via Unified Modeling Language (UML) modeling and Logical Record Structure (LRS), utilizing MySQL as the database server. Functionality testing and satisfaction surveys indicate that the information system is highly viable for implementation, achieving a respondent acceptance rate of 96% or higher. Implementation of this system has successfully eliminated manual bureaucratic processes and enhanced transparency regarding invoice status at PT HPI-Agro.